Progress of Clinical Research on the Treatment of Chronic Kidney Disease based on Kidney Collateral Theory - Bai, Tingting; Tian, Yun (Journal of Contemporary Medical Practice, 2025)
Chronic kidney disease (CKD) is a common chronic disease in clinic, and medical practitioners of all times have made unremitting explorations on its pathogenesis as well as its treatment, and kidney collateral theory is one of them. Due to the accumulation of various pathological factors in the kidney collateral, the kidneys are damaged to different degrees. Most doctors believe that chronic kidney disease is characterized by renal deficiency and stagnation of the renal channels, so the two methods of “Dredging” and “tonifying” are the key to the treatment of this disease.